Poligami (Telaah Hermeneutika Perspektif Teori Batas Muhammad Shahrur) - Syufa'at, Syufa'at (Al-Manahij: Jurnal Kajian Hukum Islam, 2008)
Shahrur’s theory stated that there are some certain conditions for doing polygami; widow with children should be the second, third or fourth; there should be fairness among children and wives.